As benzedeiras da cidade de Irati: suas experiências com o mundo e o mundo da benzeção - Vaz, Vania (2006)
This research, "Faith Healers: their life experiences and the life of healing", is a narrative study of some Faith Healers who reside in the city of Irati, located in the Central-Southern region of Paraná State. The objectives of this project are the reflection about different aspects of these women s life experiences, the influence of their social relations in the development of their practices, as well as the representation of their multiple actions, which include the Faith Healers daily lives, their personal views, and their particular way of interpreting the universe, which involves the healing rituals. Such a universe is marked by demonstrations of religiousness and faith, which can also include other actions: the discovery and/or development of the Gift, connections with protective divine entities, the development of specific rituals, besides the meaning of the Christian and social roles performed by the healers in their service, which are interpreted in a particular way by each one of the possessors of the Gift of Healing.